The Alternative Assessment of EFL Students’ Oral Competence: Practices and Constraints - Nikmah Sistia Eka Putri; Bambang Widi Pratolo; Fatimah Setiani (Ethical Lingua: Journal of Language Teaching and Literature, 2019)
This study investigates the current practices and challenges of alternative assessment for the teachers. While oral competence remains a productive skill in learning language process, the concept of alternative assessment or teacher-made assessment (classroom assessment) is another more authentic method of assessments which is different from the traditional ones. This study involved two EFL teachers who had more than five years teaching experience and used to give alternative assessment practice in the same Islamic Boarding School (IBS). An in-depth semi-structured interview and class observation was conducted with these two key aims: (1) to describe how English teachers are currently using alternative assessment practices on EFL students’ oral competence; and (2) to describe the difficulties faced by English teachers in implementing alternative assessment on EFL students’ oral competence. The results revealed that English Teacher in IBS has widely employed several methods such as peer assessment in collaborative work, and class students’ observation. In applying alternative assessment strategies, the teachers focused on oral skills which used many group activities and gave authentic materials as topic. The teachers increased the students’ involvement by giving activities such as role-play, assigning them to memorize short dialogue, drama, conversation, and presentation. The teachers also collected students’ notebooks as additional scores, raised students’ cases or problems to solve, and shared the components that would be assessed. The teachers gave some recommendations in order to use oral presentation to stimulate students’ oral competencies in their class and evaluate or control students to practice English outside of the classrooms as well. English teachers also faced several difficulties in implementing alternative assessment on EFL students’ oral competence, such as students’ lack of vocabulary, students’ weak of pronunciation and grammar which makes the students less confidence and motivation, and some slow-learners. In addition, teachers also had limited time to assess all student competencies.